Dimeric [Mo2S12]2− Cluster: A Molecular Analogue of MoS2 Edges for Superior Hydrogen‐Evolution Electrocatalysis. (20th October 2015) - Huang, Zhongjie; Luo, Wenjia; Ma, Lu; Yu, Mingzhe; Ren, Xiaodi; He, Mingfu; Polen, Shane; Click, Kevin; Garrett, Benjamin; Lu, Jun; Amine, Khalil; Hadad, Christopher; et al.
Abstract: Proton reduction is one of the most fundamental and important reactions in nature. MoS2 edges have been identified as the active sites for hydrogen evolution reaction (HER) electrocatalysis. Designing molecular mimics of MoS2 edge sites is an attractive strategy to understand the underlying catalytic mechanism of different edge sites and improve their activities. Herein we report a dimeric molecular analogue [Mo2 S12 ] 2−, as the smallest unit possessing both the terminal and bridging disulfide ligands. Our electrochemical tests show that [Mo2 S12 ] 2− is a superior heterogeneous HER catalyst under acidic conditions. Computations suggest that the bridging disulfide ligand of [Mo2 S12 ] 2− exhibits a hydrogen adsorption free energy near zero (−0.05 eV). This work helps shed light on the rational design of HER catalysts and biomimetics of hydrogen‐evolving enzymes.